Patient perspectives of lithium and quetiapine augmentation treatment in treatment-resistant depression: A qualitative assessment. (May 2022) - McKeown, Lucas; Taylor, Rachael W; Day, Elana; Shah, Rupal; Marwood, Lindsey; Tee, Helena; Kerr-Gaffney, Jess; Oprea, Emanuella; Geddes, John R; McAllister-Williams, R Hamish; Young, Allan H; Cleare, Anthony J
Background: Treatment-resistant depression (TRD) has a profound cost to patients and healthcare services worldwide. Pharmacological augmentation is one therapeutic option for TRD, with lithium and quetiapine currently recommended as first-line agents. Patient opinions about pharmacological augmentation may affect treatment outcomes, yet these have not been systematically explored. Aims: This study aimed to qualitatively assess patient experiences of lithium and quetiapine augmentation. Methods: Semi-structured interviews were conducted with 32 patients from the ongoing lithium versus quetiapine open-label trial comparing these augmentation agents in patients with TRD. Interviews were audio recorded, transcribed and a thematic analysis was used to assess patient opinions of each agent. Results: Four main themes were generated from the thematic analysis: 'Initial concerns', 'Experience of side effects', 'Perception of treatment efficacy' and 'Positive perception of treatment monitoring'. Patient accounts indicated a predominantly positive experience of lithium and quetiapine augmentation. Greater apprehension about side effects was reported for lithium prior to treatment initiation, but greater experience of negative side effects was reported for quetiapine. Clinical monitoring was perceived positively. Conclusion: Patient accounts suggested treatment augmentation with lithium or quetiapine was acceptable and helpful for most patients. However, anticipation and experiences of adverse side effects may prevent some patients from benefitting from these treatments.